Kepatuhan Penggunaan Masker Mahasiswa Akper YPPP Wonomulyo Terhadap Pencegahan Corona Virus Disease (Covid 19) - Hamsah, Idawati Ambo; Darmiati, Darmiati; Nur, Hamdan; Mardaeni, Mardaeni (Mando Care Jurnal, 2023)
Covid-19 or severe acute respiratory syndrome corona virus 2 (sars-cov-2) is a virus attacking the respiratory system. Corona virus can cause disorders in the respiratory system, acute pneumonia, to acute virus syndrome. Cov-2) which is more known with the corona virus is a new type of coronavirus that is transmitted to humans. This virus cannot attack anyone, both babies, children, adults, elderly, pregnant women, or breastfeeding mothers. Death rate also still continue to happen even in balanced with the number of patient currency. The world health problem that is currently in the spotlight and is very important to get the attention of health scientists and the general public is a disease caused by the corona virus. This research contains compliance with the use of masks for the prevention of COVID-19 at the YPPP Wonomulyo Akper campus, Polewali Mandar Regency, which is located in the eastern part of the Sidodadi Village area. The purpose of this study was to find out about covid 19 and its prevention, to get appropriate information regarding student compliance regarding the use of masks that are good and correct for preventing covid 19 at the YPPP Wonomulyo Akper campus. The method used is a descriptive survey with a cross sectional study approach. This research was conducted door to door involving 40 samples with the results obtained as follows. The average score who compliance with the use of mask are 33 respondents (82.5%) and 7 respondents who do not compliance (17.5%).